Studies on the Pathogenesis of the Generalized Shwartzman Reaction - Rodríguez-Erdmann, F (Thrombosis and Haemostasis, 1964)
Animals treated in the conventional form to elicit the generalized Shwartzman reaction (gSr) by means of properly spaced injections of endotoxin develop an abrupt consumption of the plasmatic factors of the clotting mechanism, as demonstrated by the reduction of the activity of prothrombin and Ac-G (factor V). These animals show ultimatly characteristic morphological pattern: bilateral cortical necrosis of the kidney. Rabbits treated four hours after the second (‘‘provocative”) endotoxin injection with streptokinase (Varidase/Lederle) in order to activate the fibrinolytic system failed to develop the renal cortical necrosis, but their prothrombin and Ac-G (factor V) level decreased abruptly.Through indirect deduction the intravascular presence of thrombin-like activity is accepted four hours after the “provocative” endotoxin injection.